2018
DOI: 10.1186/s41016-018-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of pineal cysts—a radiographic study

Abstract: Background: Pineal cysts (PCs) are a benign lesion of the pineal gland that have been known to the medical community for a long time. With a prevalence rate of approximately 1% in the general population, PC is often a reason for medical counseling. The natural course of PC morphology has not been well described. In this study, we present a longitudinal magnetic resonance imaging (MRI) study of patients with PCs, with special focus on those who showed an increase or decrease in PC size. Methods: We enrolled all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, notably, the 2 youngest PC apoplexy patients treated expectantly later required surgical resection due to a symptom recurrence from a second hemorrhagic event [6 , 7] . A recent study also demonstrated that patients with enlarging PCs were significantly younger than patients who's PC shrunk over time [32] . The clinician should remain aware of this fact during follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…However, notably, the 2 youngest PC apoplexy patients treated expectantly later required surgical resection due to a symptom recurrence from a second hemorrhagic event [6 , 7] . A recent study also demonstrated that patients with enlarging PCs were significantly younger than patients who's PC shrunk over time [32] . The clinician should remain aware of this fact during follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Among the majority of patients with an asymptomatic pineal cyst, the wait-and-see strategy is proper. In MRI follow-up the significant growth of lesions occurs in 5-11,4% of patients, whereas a decrease in 7,5% [6,7] . The scientific literature reports even a case of spontaneous involution of the pineal cyst [8].…”
Section: Introductionmentioning
confidence: 94%
“…Coexistent intracranial midline cysts Case Report Tiryakioglu they are smaller than 1 cm [1] with a prevalence of 1% of the population, however the size might increase by the time (particularly in the age group 6-12 years) and may become a surgical indication depending the underlying reasons [8].…”
Section: Marmara Medical Journalmentioning
confidence: 99%